Determining the Shear Strength Properties of a Soil-geogrid Interface Using a Large-scale Direct Shear Test Apparatus - Stacho, Jakub; Sulovska, Monika; Slavik, Ivan (Periodica Polytechnica Civil Engineering, 2020)
The paper deals with the laboratory testing of coarse-grained soils that are reinforced using a geogrid. The shear strength properties were determined using a large-scale direct shear test apparatus. The tests were executed on original as well as on reinforced soil, when the geogrid was placed on a sliding surface, which permitted determining the shear strength properties of the soil-geogrid interface. The aim of the tests was to determine the interface shear strength coefficient α, which represents the ratio of the shear strength of the soil-geogrid interface to the unreinforced soil. The tests were executed on 3 samples of coarse-grained materials, i.e., poorly graded sand, poorly graded fine gravel and poorly graded medium gravel. Two types of geogrids were tested, i.e., a woven polyester geogrid and a stiff polypropylene geogrid. The results of the laboratory tests on the medium gravel showed that the reduction coefficient α reached higher values in the case of the stiff polypropylene geogrid. In the cases of the fine gravel and sand, the values of the interface coefficient α were similar to each other. The shear strength of the interface was reduced or was similar to the shear strength of unreinforced soil in a peak shear stress state, but significantly increased with horizontal deformations, especially for the fine gravel and sand. The largest value of the coefficient α was measured in the critical shear stress state. Based on the results of the testing, a correlation which allows for determining the optimal grain size distribution was obtained.